Adaptive variable impedance control of dual-arm robots for slabstone installation. (September 2022) - Hu, Heyu; Cao, Jianfu
Abstract: The conventional dual-arm cooperative control method employed in the construction field cannot adequately meet the requirements of high precision and adaptability because of the use of large objects, heavy load, unstructured environment, and constraints related to the complex operation processes involved. Dual-arm robots are highly complex multi-degree-of-freedom system, and when using this robots for slabstone installation, it is necessary to consider not only the position constraint and force coupling relationship of the closed chain system, but also the force/position control while the slabstone contacts the wall. To solve this problem, this paper presents slabstone-installation model and motion element decomposition for dual-arm robots. Moreover, a control strategy is proposed by combining an adaptive variable impedance tracking controller for the force/position control of the slabstone and a tracking controller for the end-effector trajectories of the dual arms; the controllers proposed meet the requirements of position tracking and contact force tracking of the slabstone. Finally, different slabstone installation scenarios are simulated to verify the effectiveness of the proposed algorithm. The results show that the algorithm is compliant for the slabstone installation process and can meet the requirements of force/position control. Highlights: An adaptive impedance control method with variable stiffness coefficient is proposed for coordinated operation of dual-arm robots to achieve position/force control. A trajectory controller of the robot is designed based on position feedback, which does not require any complex operation process and has a small amount of calculation. A control strategy combining the coordination controller and the trajectory tracking controller is proposed.